2006
DOI: 10.1111/j.1365-2095.2006.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary cornstarch levels on growth performance, digestibility and microscopic structure in the white shrimp, Litopenaeus vannamei reared in brackish water

Abstract: The ability of Litopenaeus vannamei (initial mean weight: 0.96 ± 0.02 g) to utilize different levels of cornstarch was examined in terms of growth indices, body composition, digestibility and microscopic structure of the hepatopancreas. Six isonitrogenous semipurified diets were fed to satiation to shrimp for 8 weeks in triplicate tanks (30 shrimps per tank) connected to a natural brackish water (6–8 g L−1) recirculating system. Diets contained different levels of cornstarch (100, 150, 200, 250, 300 and 350 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
59
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 21 publications
8
59
0
3
Order By: Relevance
“…There would be an increasing lipid accumulation in the whole body and hepatopancreas associated with enhanced levels of dietary cornstarch. Similar results were obtained by Guo et al (2006).…”
Section: Treatmentsupporting
confidence: 81%
See 4 more Smart Citations
“…There would be an increasing lipid accumulation in the whole body and hepatopancreas associated with enhanced levels of dietary cornstarch. Similar results were obtained by Guo et al (2006).…”
Section: Treatmentsupporting
confidence: 81%
“…Shiau and Peng (1992) found that P. monodon fed with a diet containing 100 g kg −1 of starch grew more efficiently. Guo et al (2006) indicated that the maximum growth rate of Litopenaeus vannamei was achieved in shrimps fed with diets containing 100-200 g kg −1 of cornstarch. In the present study, it was found that P. clarkii fed with diets containing 200 g kg −1 of cornstarch showed the best growth performance and feed utilization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations